Electrocardiographic and morphometric features in patients with ventricular tachycardia of right ventricular origin - Kazmierczak, J (1998)
Objective—To study differences between repetitive monomorphic ventricular tachycardia (RMVT) of right ventricular origin, and ventricular tachycardia in arrhythmogenic right ventricular dysplasia (ARVD). Patients—Consecutive groups with RMVT (n = 15) or ARVD (n = 12), comparable for age and function. Methods—Analysis of baseline, tachycardia, and signal averaged ECGs, clinical data, and right endomyocardial biopsies. Pathological findings were related to regional depolarisation (QRS width) and repolarisation (QT interval, QT dispersion). Results—There was no difference in age, ejection fraction, QRS width in leads I, V1, and V6, and QT indices. During ventricular tachycardia, more patients with ARVD had a QS wave in V1 (p < 0.05). There were significant differences for unfiltered QRS, filtered QRS, low amplitude signal duration, and the root mean square voltage content. In the absence of bundle branch block, differences became non-significant for unfiltered and filtered QRS duration. Mean (SD) percentage of biopsy surface differed between RMVT and ARVD: normal myocytes (74(3.4)% v 64.5(9.3)%; p < 0.05); fibrosis (3(1.7)% v 8.9(5.2)%; p < 0.05). When all patients were included, there were significant correlations between fibrosis and age (r = 0.6761), and fibrosis and QRS width (r = 0.5524 for lead I; r = 0.5254 for lead V1; and r = 0.6017 for lead V6). Conclusions—The ECG during tachycardia and signal averaging are helpful in discriminating between ARVD and RMVT patients. There are differences in the proportions of normal myocytes and fibrosis. The QRS duration is correlated with the amount of fibrous tissue in patients with ventricular tachycardia of right ventricular origin.   Keywords: arrhythmogenic right ventricular dysplasia;  electrocardiography;  endomyocardial biopsy;  ventricular arrhythmias